Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Zhai, Changchun; Han, Lili; Xiong, Chao; Ge, Anhui; Yue, Xiaojing; Li, Ying; Zhou, Zhenxing; Feng, Jiayin; Ru, Jingyi; Song, Jian; Jiang, Lin; Yang, Yunfeng; et al. (The Science of the total environment, 2024)
Soil microbiomes play a critical role in regulating ecosystem multifunctionality. However, whether and how soil protists and microbiome interactions affect ecosystem multifunctionality under climate change is unclear. Here, we transplanted 54 soil monoliths from three typical temperate grasslands (i.e., desert, typical, and meadow steppes) along a precipitation gradient in the Mongolian Plateau and examined their response to nighttime warming, decreased, and increased precipitation. Across the three steppes, nighttime warming only stimulated protistan diversity by 15.61 (absolute change, phylogenetic diversity) but had no effect on ecosystem multifunctionality. Decreased precipitation reduced bacterial (8.78) and fungal (22.28) diversity, but significantly enhanced soil microbiome network complexity by 1.40. Ecosystem multifunctionality was reduced by 0.23 under decreased precipitation, which could be largely attributed to the reduced soil moisture that negatively impacted bacterial and fungal communities. In contrast, increased precipitation had little impact on soil microbial communities. Overall, both bacterial and fungal diversity and network complexity play a fundamental role in maintaining ecosystem multifunctionality in response to drought stress. Protists alter ecosystem multifunctionality by indirectly affecting microbial network complexity. Therefore, not only microbial diversity but also their interactions (regulated by soil protists) should be considered in evaluating the responses of ecosystem multifunctionality, which has important implications for predicting changes in ecosystem functioning under future climate change scenarios. [Display omitted] •Decreased precipitation reduced microbial diversity but elevated network complexity.•Ecosystem multifunctionality (EMF) increased with bacterial and fungal diversity.•EMF showed negative dependence upon microbial network complexity.•Protists indirectly affect EMF by altering bacteria-fungi interactions.